Zero-echo time magnetic resonance imaging for visualizing pulmonary neoplasms - Yanjie Zhao; Zhipeng Hao; Weiyin Vivian Liu; Yujin Wang; Shuchang Zhou; Liming Xia (BMC Medical Imaging)
Abstract Objective To assess the ability of a zero-echo time sequence combined with a highly flexible adaptive image receiving coil (AIRTM coil) to visualize pulmonary neoplasms. Methods A total of 42 patients with pulmonary neoplasms were included, all of whom underwent chest CT and MRI examinations. A highly flexible AIRTM coil was used. The MR-ZTE and CT images were compared in terms of subjective and objective image quality. Results Intrapulmonary structures were imaged using MRI-ZTE. Various nodules and masses, including micronodules, subsolid or ground glass opacification nodules, and various masses, were clearly visualized via MRI-ZTE. In terms of subjective image quality, there was no significant difference in lesion detectability between CT and MRI-ZTE (P = 0.8). In terms of objective image quality for MRI-ZTE, the SNRs and CNRs of the lung parenchyma, pulmonary nodules, trachea, peripheral bronchus, and peripheral pulmonary vessels were good. Conclusions MRI-ZTE enabled the detection of intrapulmonary structures and various pulmonary neoplasms with good image quality, including micronodules, subsolid or ground glass opacification nodules, and various masses. Therefore, MRI-ZTE has great potential as a nonradiation alternative to CT for the follow-up of pulmonary neoplasms.